Optically pumped non-zero field magnetometric sensor for the magnetoencephalographic systems using intra-cavity contacted VCSELs with rhomboidal oxide current aperture. (December 2020) - Bobrov, M A; Blokhin, S A; Maleev, N A; Blokhin, A A; Vasyl'ev, A P; Kuzmenkov, A G; Pazgalev, A S; Petrenko, M V; Dmitriev, S P; Vershovskii, A K; Ustinov, V M; Novikov, I I; et al.
Abstract: We demonstrate the possibility of using vertical-cavity surface emitting lasers with intracavity contacts and a rhomboidal oxide current aperture for creating compact optically pumped 133 Cs atomic magnetometer operating in non-zero magnetic fields, which is promising to use in magnetoencephalographic systems. The magnetic resonance parameters were studied in a two-beam MX optically pumped magnetic field sensor scheme based on the effect of the magnetic resonance line narrowing at high laser pumping and high concentrations of alkali-metal atoms. The ultimate sensitivity of OPM was estimated by the ratio of the magnetic resonance steepness to the probe light shot noise level. It is shown that a magnetic sensor based on the vertical-cavity surface emitting lasers and a compact (0.125 cm 3 volume) Cs vapor cell can achieve a shot noise-limited sensitivity better than 15 fT in 1 Hz bandwidth. Developed intracavity contacted VCSELs suitable for use in compact atomic magnetometers for magnetoencephalographic systems.